Weathering Performance of Wood Coated with a Combination of Alkoxysilanes and Rutile TiO2 Heirarchical Nanostructures - Rongbo Zheng; Mandla A. Tshabalala; Qingyu Li; Hongyan Wang (BioResources, 2015)
The weathering performance of wood coated with a combination of rutile TiO2 hierarchical nanostructures and a sol-gel deposit of alkoxysilanes was determined by exposing three sets of specimens to UV light and water spray. The first set consisted of specimens coated with a mixture of methyltrimethoxysilane (MTMOS) and hexadecyltrimethoxysilane (HDTMOS). The second set consisted of specimens coated with nanostructural TiO2 followed by a mixture of MTMOS and HDTMOS. The third set consisted of uncoated control specimens. The wood coated with TiO2 followed by a mixture of MTDMOS and HDTMOS exhibited significantly less surface color change and weight loss as a result of UV light-induced degradation and erosion from water spray in comparison with the other groups. However, the coated surfaces were gradually transformed from hydrophobic to hydrophilic. Despite this apparent weakness, the MTMOS/HDTMOS/TiO2 coating, with superior photostabilization properties and resistance to surface erosion, may be useful for improving the weathering performance of wood coated with semi-transparent wood stains.